Exclusionary Inclusion? Peace Agreements and Provisions on Child Protection - Molloy, Sean (Nordic journal of human rights, 2023)
Peace agreements often serve as roadmaps for peacebuilding and the reconstruction of the post-conflict state. They do this by, among other things, delineating issues to be addressed as part of the transition from conflict to peace, reforms to be enacted, and the groups that are to benefit from them. It follows that what and who is included in a peace agreement matters. Often overlooked in the scholarship, however, are the potential implications-positive and negative-of the language adopted in peace agreements. With attention to language, this article examines how peace agreements address a particular but salient issue: child protection. It first provides an overview of existing provisions on the subject before contemplating the disempowering potential of the terminology used. The article demonstrates the need for more clarity in how commitments are constructed in peace agreements.